Validations of Top and Novel Susceptibility Variants in All-Age Chinese Patients With Acute Lymphoblastic Leukemia - Liao, Fei; Ye, Yuanxin; Yin, Dandan; Qin, Yun; Zhao, Jiangyan; Zhang, Wanhua; Zhang, Yan; Deng, Zhujun; Wang, Yuelan; Ying, Binwu; Wang, Lanlan; Gao, Ju; et al. (Frontiers in Genetics, 2020)
Through genome-wide association studies (GWAS), multiple inherited predispositions to acute lymphoblastic leukemia (ALL) have been identified in children. Most recently, a novel susceptibility locus at ERG was localized, exhibiting Hispanic-specific manner. In this study, we conducted a replication study to in all-age Chinese patients (N=451), not only validating the novel ERG locus, but also systematically determining the impact of age on association status of the top GWAS signals. We found that single nucleotide polymorphisms at ARID5B, IKZF1, CEBPE, PIP4K2A were only significantly associated with ALL susceptibility in childhood patients with no BCR-ABL fusion, while GATA3 signal exhibited its significance in adults no matter carrying BCR-ABL fusion or not. Moreover, the novel ERG SNP can be validated in pediatric patients without both BCR-ABL and ETV6-RUNX1 fusion. Our finding suggests the modifying effects of age on genetic predisposition to ALL, and highlights the impact of ERG SNP in Chinese patients.